Macro anatomical investigation of brachial plexus of the White New Zealand rabbit (Orycotolagus cuniculus) - Mohiuddin, M; Rahman, ML; Alim, MA; Kabir, MBH; Kashem, MA (International Journal of Natural Sciences, 2011)
In present study, the brachial plexus of the White New Zealand rabbit (Orycotolagus cuniculus) was investigated. Five adult rabbits were used and organizations of the brachial plexus of them were investigated. It was found that the brachial plexus of the rabbit was formed by rami ventralis of fifth cervical spinal nerve (C5), sixth cervical spinal nerve (C6), seventh cervical spinal nerve (C7), eighth cervical spinal nerve (C8), first thoracic spinal nerve (T1) and second thoracic spinal nerve (T2). The rami ventralis of C5 spinal nerve and T2 spinal nerve were divided into two branches. The caudal branch of C5 spinal nerve and cranial branch of T2 spinal nerve contributed to the brachial plexus. The caudal branch of C5 spinal nerve and C6 spinal nerve constituted the cranial trunk and the caudal trunk was formed by a branch which came from cranial trunk, rami ventralis of C7, C8, T1 spinal nerves and the cranial branch of ventral ramus of T2 spinal nerve. Contribution of caudal branch of ventral ramus of C5 spinal nerve and cranial branch of ventral ramus of T2 spinal nerve to the formation of the brachial plexus of rabbit and division of the brachial plexus to the caudal and cranial trunks resemble to porcupine and differ the brachial plexus of this species from those of rat, mouse and mammals. Key words: Spinal nerves; Orycotolagus cuniculus; Brachial plexus; Rabbits. DOI: http://dx.doi.org/10.3329/ijns.v1i3.8825 International Journal of Natural Sciences (2011), 1(3):74-76